Is a Preservation Solution for Living Donor Liver Transplantation Needed? Adding a New Chapter in LDLT!. Issue 11 (7th October 2022) - Dogar, Abdul Wahab; Ullah, Kaleem; Shams-ud-din,; Abbas, Syed Hasnain; Hussain, Azhar; Ghaffar, Abdul; Bilal, Hafiz; Siraj-ud-din,; Shoaib, Azam; Ahmed, Bilal; Raza, Hamid; Hamza, Ameer; et al.
Abstract : Background: Preservation solutions are required for organ viability in deceased donor liver transplantation (LT). However, their role in live donor LT (LDLT) has not been standardized. Methods: Eighty adult recipients who underwent right lobe LDLT at the Department of Liver Transplantation Surgery, Gambat, Pakistan, were studied. Based on shorter cold ischemia time and no back table reconstruction work, recipients were assigned to receive "no preservation solution" (cases/non–histidine-tryptophan-ketoglutarate group; n = 40) or "HTK group" (controls; n = 40). Early allograft dysfunction (bilirubin, transaminases, and international normalized ratio), postoperative complications (biliary and vascular), hospital stay, and 1-y survival were reported. The direct cost was also reported. Results: Demographics and clinical characteristics were comparable in the 2 groups. Comparing cases versus controls, mean bilirubin, alanine aminotransferase, aspartate aminotransferase, and international normalized ratio on postoperative day 7 were similar in the 2 groups. Five (12.5%) cases and 4 (10%) controls developed early allograft dysfunction ( P = 0.72). Post-LT complications (biliary leak 2.5% in cases versus 0 in control), strictures (15% in cases versus 17.5% in controls), hepatic artery thrombosis (2.5% versus 00%)‚ and portal vein thrombosis (0 versus 2.5%) were comparable. Mean hospital stay (10.80 + 2.36 and 11.78 + 2.91 d) and 30 d mortality (2.5% versus 5%) were also comparable. Finally, 1-y survival based on Kaplan-Meier analysis was comparable in both groups (ie, 92.5%; non-HTK group versus 90%; HTK group) ( P = 0.71). The direct cost of using a non-HTK–based approach was less than the HTK solution. Conclusion: In a selected cohort of right lobe LDLT recipients, preservation solutions can be avoided safely with comparable outcomes.